Gutman Index and Harary Index of Unitary Cayley Graphs - Philipose, Roshan; P B, Sarasija (International Journal of Engineering and Technology, 2018)
In this paper, we determine the Gutman Index and Harary Index of Unitary Cayley Graphs. The Unitary Cayley Graph Xn is the graph with vertex set  V(Xn) ={u|u∈ Zn} and edge set {uv|gcd(u−v, n) = 1 and u, v ∈ Zn }, where Zn ={0,1,...,n−1}.